Restarting the tuberculosis programme post-Haiyan - Woojin Lew; Rosalind Vianzon; Anna Maria Celina Garfin; Julie Lyn Hall (World Health Organization Regional Office for the Western Pacific, 2015)
Problem: Typhoon Haiyan damaged or destroyed health infrastructure, equipment and services essential to the Philippine National Tuberculosis Programme (NTP), and it had to be re-established in the affected areas in Regions 6, 7 and 8. Continuing treatment and restoring diagnostic capacity were also challenging. Context: The Philippines has one of the highest tuberculosis (TB) burdens in the world. At the time of Typhoon Haiyan, there were an estimated 26 600 TB cases on treatment at directly observed treatment, short-course (DOTS) centres and 356 multidrug-resistant TB cases registered at programmatic management of drug-resistant TB (PMDT) sites. As TB was not included in the Philippines early-warning post-disaster surveillance system, tracking TB patients was difficult after Haiyan. Actions and outcomes: Immediately following Haiyan, each aspect of the NTP was assessed to determine the extent of damage. TB patients were traced and services restored. We created maps showing the location of temporary TB diagnostic and treatment services, which hastened referrals. We provided new laboratory equipment, training and rapid testing capabilities in the affected regions. All TB services in the affected areas (473 DOTS, 490 TB microscopy and six PMDT facilities) were restored just two months after Haiyan. Lessons learnt: Key lessons learnt from the NTP experience following Tyhoon Haiyan were: (1) the importance of having an electronic TB registry (database); (2) the need to include TB in the post-disaster surveillance system; (3) clear guidelines for TB control in disasters; and (4) the importance of coordination with all partners.